Agricultural Marketing in the wake of the World Trade Agreement - K.H. Vedini, (Journal of Agricultural Extension Management, 2025)
For India and the other developing countries, liberalization is an advantage. Initially, many economists were optimistic about being apart of the global village. As time panes, more challenges are coming up leading to more confusion. Given this backdrop, it would be appropriate to collate the relationship between two and its interlinked opportunities in view of open trade policy